Smart citizens for Smart cities: the role of social media for expanding local democracy (The case of local referendums in Bulgaria) - Bissera ZANKOVA (Smart Cities and Regional Development Journal)
The purpose of the study is to analyze the role of social media to boost democratic citizenship and contribute to the creation of smart environment through the perspective of direct democracy in Bulgaria. The issue of â€œsmart citiesâ€ will be tackled from a broader media and communication perspective. The term â€œsmart cityâ€ does not denote the symbiosis between urban development and new information technologies only but it signifies a new vibrant social ecology rooted in the thorough use of the Internet for wider democratic participation. As a theoretical basis of my survey I shall use Deweyâ€™s model of the inherent bond between communication and enlightened citizenry and Robert Putnamâ€™s theory about the social capital facilitated by social networks generating trust and solidarity among community members. As a case study I shall dwell on local democracy and particularly on two recent referendums in Bulgaria (2017) - in the cities of Tran and Stara Zagora, their basic premises, claims, organization, social media use, outcomes and impact. Though not mandatory for the governing bodies the referendumsâ€™ results demonstrated the level of social activity in the country underpinned by networks.  Democracy should be understood best through the Abraham Lincolnâ€™s centuries-cherished metaphor as â€œgovernment of the people, by the people, for the peopleâ€. In the current research I build on a previous investigation done in 2013 on civic journalism, blogs and protests in Bulgaria and on my contribution to the book â€œSmart journalismâ€ (Zankova, Skolkay, Franklin (2016), presenting findings from the New Media Literacy Project 2012 - 2014. This interdisciplinary paper will be useful for both academics and practitioners and specifically for media specialists who will get knowledge about the state of direct democracy in a new democratic country in SEE, new media non/ contribution to this state and what the necessary conditions are to make this democracy really workable at a community level to turn the cities into future-oriented democratic centres.